2011
DOI: 10.1177/0731684411415451
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic, tomographic, and morphological properties of bismaleimide-modified PLA green composites

Abstract: The effect of N 0 -(o-phenylene)dimalemide and 2,2 0 dithiobis(benzothiazole) on the speed of sound, sound attenuation and loss factor, 3-D microstructure, fiber dispersion, and morphology of wood pulp-reinforced PLA composites produced by hot press was investigated. Analysis of the chemical composition and fiber length of the wood pulp fibers provided information about the mechanism of adhesion and crystallinity of the modified composites. It was found that the modified composites have quite similar sound att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Therefore, improvement of interface adhesion and reduction of fiber polarity were able to effectively prevent the aggregation between the fibers, thereby enhancing fiber dispersion in the matrix. Raj et al 24 and Baltazar-y-Jimenez et al 25 had found the same result in their studies. From this table, with the same extrusion compounding, the tensile properties of composites were increased greatly with fiber treatments and the incorporation of MAPP, which mainly attributed to the improvement of interface adhesion and uniform fiber distribution.…”
Section: Fiber Distribution and Tensile Propertiessupporting
confidence: 57%
“…Therefore, improvement of interface adhesion and reduction of fiber polarity were able to effectively prevent the aggregation between the fibers, thereby enhancing fiber dispersion in the matrix. Raj et al 24 and Baltazar-y-Jimenez et al 25 had found the same result in their studies. From this table, with the same extrusion compounding, the tensile properties of composites were increased greatly with fiber treatments and the incorporation of MAPP, which mainly attributed to the improvement of interface adhesion and uniform fiber distribution.…”
Section: Fiber Distribution and Tensile Propertiessupporting
confidence: 57%
“…Larger difference between the theoretical values and the experimental results were observed for hybrid biocomposites. From the literature, this can be attributed to poor fiber–matrix adhesion or increased microstructure defects, and higher void frequency . These results suggest that hybrid biocomposites will exhibit less than optimal mechanical and thermal performance.…”
Section: Resultsmentioning
confidence: 99%
“…Sound absorption property of hybrid biocomposites were measured using scanning acoustic microscopy (SAM) at transmission frequency of 1–15 MHz as explained by Baltazar‐y‐Jimenez et al . For determination of fogging characteristics, SAE J1756 standard (photometric method) was used in Labthink FT‐F1 fogging tester.…”
Section: Methodsmentioning
confidence: 99%
“…Now, many components of automobiles are fabricated using natural fiber based composites. [9][10][11][12] Polylactic acid (PLA), a corn derived, fully biodegradable polymer based natural fiber green composite, is becoming popular in existing areas of application, especially in exterior and interior components of automobiles. Though PLA is biodegradable and provides good esthetics and has good mechanical properties and easy processability, it is brittle in nature which limits its application in various areas.…”
Section: Introductionmentioning
confidence: 99%